2022
DOI: 10.3389/fenvs.2022.875577
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Environment in Uruguay: The Roles of Financial Development, Natural Resources, and Trade Globalization

Abstract: As the world continues to be a globalized society, there have been variations in environmental quality, but studies including trade globalization into the environmental policy framework remain inconclusive. Therefore, employing the time series dataset of Uruguay over the period between 1980 and 2018, the main objective of this current study is to investigate the effect of trade globalization, natural resources rents, economic growth, and financial development on carbon emissions. By employing the bounds testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 52 publications
2
24
1
Order By: Relevance
“…The study found a connection between long-term increases in CO 2 emissions and increases in economic growth, but this connection does not exist in the short term. Additionally, it was discovered that technological advances were responsible for a portion of the decrease in CO 2 emissions (Awosusi et al, 2022b ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found a connection between long-term increases in CO 2 emissions and increases in economic growth, but this connection does not exist in the short term. Additionally, it was discovered that technological advances were responsible for a portion of the decrease in CO 2 emissions (Awosusi et al, 2022b ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, they established the evidence of the EKC hypothesis. The work of Awosusi et al [39] in Uruguay detected that the upsurge in natural resources intensifies CO 2 emissions. Conversely, using the panel dataset spanning from 1990-2018, the investigation of Tufail et al [40] in seven selected nations testified that the increase in NR curbs the level of degradation in the environment.…”
Section: Research Hypothesis 3 (H3)mentioning
confidence: 99%
“…e research was particularly interested in the opportunities and problems faced by Romanian institutions during COVID-19 in terms of knowledge distribution. It gave us a thorough look at the technical issues that frequently arise in online communication, such as instructors' lack of technological skills [26][27][28].…”
Section: Literature Reviewmentioning
confidence: 99%